Corporate Governance Enhances the Performance of Financial Institutions: A Comparative Study on Banking Industry of Bangladesh - Datta, Rajib; Barua, Sujoy; Mawa, Jannatul (Archives of Business Research, 2023)
Corporate Governance refers to the manner by which organizations are administered and to what reason. It distinguishes who has power and responsibility, and who simply decides. Corporate Governance has become visible noticeably over the world particularly in business regions like banks, NBFIs, insurances, administrative bodies, and autonomous bodies. This study intends to critically notice the exhibition of financial institutions improved by ensuring great corporate governance and what are the deterrents holding behind to accomplish it. From this examination we can gather that, various sorts of financial scams and advance defaulting hampering the business enormous. We had compared information gathered from 20 banks including both conventional and Islamic bank contrasting year 2020 with year 2022 recorded and controlled under Bangladesh Bank’s administration. The corporate governance practices in Bangladesh have been largely limited to financial Sector and the Banking sector can serve as a motivation for better corporate governance through its requirements and procedures for approving and monitoring loans. These results suggest that better corporate governance mechanisms are imperative for every banking company and should be encouraged for the interest of the investors and other stakeholders as well as company’s both financial & operational activities.